Assistive Robotics and Muscular System Modeling for Rehabilitation of Spasticity Patients - Ramis, Marcos; Santos, Juliana; Oliveira, Vinicius (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The use of robotic rehabilitation systems allows specialists to decide on objective measures of patient progress, allowing them to program a personalized training plan. Thus, the use of assistive robotics provides individuals with rehabilitation and restoration of motor functions, if not totally, at least in part, which directly impacts their quality of life. In this work models are used to simulate muscle dynamics using EMG sensors.